2018
DOI: 10.1007/s13304-018-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Tailored treatment for signet ring cell gastric cancer

Abstract: Gastric cancer with Laurèn diffuse types is increasing in the West. The raising trend is more evident when considering signet ring cells (SRC) histology. However, to control the biologic potential of this GC subtype, some hypotheses of tailored therapeutic strategies for SRC cancers have been made. A review of the literature was performed using the key words "signet ring cells" AND "gastric cancer". Results of literature review were descriptively reported. Endoscopic submucosal dissection (ESD), according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Among the WHO type and Lauren type, signet-ring cell carcinoma and diffuse type owned the greatest risk of LNM, respectively ( Figure 4 ) due to their high lymph tropism and infiltrating behavior. Therefore, the extension of gastric resection might be more beneficial for EGC patients with diffuse type and signet-ring cell carcinoma ( 27 ). LVI, as another contraindication for ER, is easily ignored before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Among the WHO type and Lauren type, signet-ring cell carcinoma and diffuse type owned the greatest risk of LNM, respectively ( Figure 4 ) due to their high lymph tropism and infiltrating behavior. Therefore, the extension of gastric resection might be more beneficial for EGC patients with diffuse type and signet-ring cell carcinoma ( 27 ). LVI, as another contraindication for ER, is easily ignored before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, radical tumor resection (R0 resection) is still the optimal treatment ( 5 ). Due to the non-specific symptoms, such as pain or vomiting, curative resection is not suitable for most patients, resulting in a negative impact on GSRCC patients’ prognosis ( 6 ). Therefore, research on GC containing signet ring cell components becomes essential.…”
Section: Introductionmentioning
confidence: 99%
“…Japan Gastric Cancer Association (JGCA) treatment guidelines also recommends extended criteria for undifferentiated histology; however, ambiguity still persists regarding oncological safety of therapeutic endoscopic approach [60]. In the west, EGC has higher reported rate of lymph node metastasis than those reported in eastern studies [4,61]. Recent studies have also reported higher rate of lymph node spread in SRCC [62,63].…”
Section: Early Gastric Srccmentioning
confidence: 99%
“…The Italian Research Group for Gastric Cancer (GIRCG) in a retrospective study reported lower recurrence rate in advanced gastric cancer with diffuse histology following D3 lymphadenectomy [69]. Due to the lymph tropism and higher tendency for metastasis to D3 lymph nodes in diffuse histology [4,70], the role of extended lymphadenectomy needs to be established in future studies.…”
Section: Advanced Gastric/gej Srccmentioning
confidence: 99%
See 1 more Smart Citation